Speaking as both necessity and challenge: an ESP need analysis of performing art students - Haris Danial; Noerja Fadhilla Hadjaratie (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
This study identifies the English language needs of performing arts (Sendratasik) students at Universitas Negeri Gorontalo, Indonesia, within an English for Specific Purposes (ESP) framework. A mixed-methods design was employed, combining questionnaires (n=50) and semi-structured interviews (n=10) to analyze target needs (necessities, lacks, wants) and learning needs (strategies, assessment preferences, barriers). Findings reveal that speaking is the most essential skill (70.4% of students), yet paradoxically also the most difficult (55.6%). Students prefer interactive teaching methods (55.6%) and collaborative strategies such as group discussions (40.7%). However, an assessment paradox emerged: despite prioritizing speaking, 55.6% of students prefer written tests over oral assessments. Low self-confidence (55.6%) is identified as the primary psychological barrier to speaking performance. We conclude that a significant gap exists between perceived needs and actual abilities in speaking, mediated by affective factors. These findings challenge the assumption that needs awareness alone translates into competence. Pedagogically, we recommend Task-Based Language Teaching (TBLT) and Content and Language Integrated Learning (CLIL) to align instruction with students' communicative needs while reducing anxiety. This study contributes empirical evidence to the under-researched intersection of ESP and performing arts education in non-Western contexts.